Effects of asphalt binder modifying with nano hydrated lime on moisture susceptibility of asphalt mixtures with thermodynamically concepts. (16th February 2020) - Behbahani, Hamid; Hamedi, Gholam Hossein; Moghaddam Gilani, Vahid Najafi
Abstract: This study aims to investigate the effect of using Nano Hydrated Lime (NHL) as asphalt binder modifier on the moisture sensitivity of Hot Mix Asphalt (HMA) with consideration of its impact mechanism on bituminous-aggregate adhesion. In order to investigate the moisture susceptibility, the indirect tensile strength (ITS) test and the concepts of surface free energy (SFE) have been applied. To simulate environmental conditions, samples of HMA have been exposed to 1, 3 and 5 freeze-thaw cycles. The results show that the use of NHL increases the ITS values and the indirect tensile strength ratio (TSR) in both types of aggregates.